Animal farm - Orwell, George,.; Tull, Patrick (London : Penguin Books ltd, 1996)
The animals of the farmyard rebel against Farmer Jones in the name of equality.
Novel.
"Unabridged"--Container insert.
Accompanied by text: Animal farm : a fairy story / by George Orwell ; preface by Russell Baker ; introduction by C.M. Woodhouse. 50th anniversary ed. New York : Signet Classic, 1996.
Narrated by Patrick Tull.
All Ages.
Keywords: preface by russell baker